2020
DOI: 10.4149/bll_2020_051
|View full text |Cite
|
Sign up to set email alerts
|

Late effects of cutaneous 3-methylcholanthrene exposure on DNA damage-related pleiotropic growth factors and oxidative stress markers in mice

Abstract: BACKGROUND: Skin is the body's fi rst defence against direct exposure to variety of chemicals. Polycyclic aromatic hydrocarbons such as 3-methylcholanthrene (3-MC) are common in polluted urban air and have a potential of producing harmful effects. Moreover, their late effects can occur months or years after exposure. OBJECTIVES: We aimed to investigate the long-term effects of 3-MC induced dermal toxicity on the expression of markers of apoptosis, pleiotropic cytokines, and oxidative stress and to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…3-MC is a common environmental pollutant with strong toxicity and carcinogenicity; exposure to 3-MC can lead to various cancers and tumor diseases [ 3 , 4 ]. Additionally, 3-MC is an ovotoxin that can affect oocyte growth, and partial studies have revealed the effects of 3-MC on the reproductive system in small model organisms [ 17 , 18 , 19 ]. However, the toxic effects and mechanisms of 3-MC on mammalian oocyte maturation are not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3-MC is a common environmental pollutant with strong toxicity and carcinogenicity; exposure to 3-MC can lead to various cancers and tumor diseases [ 3 , 4 ]. Additionally, 3-MC is an ovotoxin that can affect oocyte growth, and partial studies have revealed the effects of 3-MC on the reproductive system in small model organisms [ 17 , 18 , 19 ]. However, the toxic effects and mechanisms of 3-MC on mammalian oocyte maturation are not known.…”
Section: Discussionmentioning
confidence: 99%
“…When cells are subjected to harmful stimuli, the oxidation–antioxidant system is unbalanced and causes a large number of reactive oxygen species (ROS) radicals to be produced, causing cell apoptosis [ 55 , 56 ]. Meanwhile, ROS can directly or indirectly oxidize/damage DNA [ 11 , 18 , 32 ]. Exposure to 3-MC disrupted the normal growth environment of oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term cytokine stems from two Greek words: cyto (cell) and kinos (movement) (7). Generally, Cytokines are low molecular weight proteins secreted by immune cells, endothelial cells, fibroblasts, and other stromal cells (8) with pleiotropic and cell-specific functions including; cellular communications and the coordination of cellular responses (9,10). Also, they provide growth, differentiation, inflammatory or antiinflammatory signals to relevant cells, and most often, they are released during defined periods in response to stimuli (11,12).…”
Section: Introductionmentioning
confidence: 99%